QUO VADIS NEGARA KESEJAHTERAAN: MENEGUHKAN IDEOLOGI WELFARE STATE NEGARA HUKUM KESEJAHTERAAN INDONESIA - E. ELVIANDRI (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2019)
AbstractThe constitution mandates the state to realize prosperity as stated in the 14th article of the 1945 Constitution, however empirically it seems to have no power for creating a prosperous society. The main goal of this article is to discuss perspectives and efforts for affirming the welfare state ideology. A conception of welfare law state of Indonesia requires that every state action or government must be based on a law, security and public order, makes the welfare state ideology as the foundation of government and its function (bestuursfunctie) in holding duties and responsibilities for the people welfare and creating social justice as the spirit of economic development. IntisariKonstitusi mengamanatkan negara mewujudkan kesejahteraan yang termaktub dalam 14 pasal Konstitusi 1945, namun dalam realitas empirisnya seakan tidak memiliki kekuatan membentuk masyarakat yang sejahtera. Artikel ini bertujuan untuk memberikan pandangan dan upaya peneguhan ideologi welfare state. Konsepsi negara hukum kesejahteraan Indonesia menghendaki setiap tindakan negara atau pemerintah harus berdasarkan hukum, menjamin keamanan dan ketertiban masyarakat, menjadikan ideologi welfare state sebagai landasan kedudukan dan fungsi pemerintah (bestuursfunctie) dalam mengemban tugas, dan tanggung jawab yang lebih luas untuk mensejahterakan rakyat serta menjadikan keadilan sosial sebagai rohnya pembangunan ekonomi.